Perencanaan Keorganisasian Bisnis dan Sumber Daya Manusia dalam Membentuk Kewirausahaan - Bima Ramadhani; Agung Winarno (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study examines business organization planning and human resource management in an effort to form an entrepreneurial spirit. The main goal is to understand how human resource management can contribute to the achievement of business goals and create resilient entrepreneurs. The method applied is a literature study by analyzing various literature related to business organizational planning, human resource management, and entrepreneurship. The results of the study show that careful planning and good human resource management can have a significant impact on organizational success while supporting the achievement of entrepreneurial goals efficiently.